Evolution of thermal and mechanical properties of Nitinol wire as a function of ageing treatment conditions - Wang, Z; Everaerts, J; Salvati, E; Korsunsky, A (Elsevier, 2019)
As-received and cold-worked 55Ni–45Ti wt% Nitinol wire samples were subjected to various ageing treatments. Experiments show that the properties of as-received Nitinol, including microstructure, critical temperatures in thermally induced phase transformation, and critical stresses/strains in mechanically induced phase transformation, change significantly after ageing process at 773 K for different durations ranging from 10 min to 5 h. BSE and EBSD/EDS analysis shows that the predominant microstructural evolution is a large increase in Ni4Ti3 precipitate volume fraction, while grain growth is negligible. DSC results show that as-received material exhibits little to no phase transformation during heating-cooling cycling at 5K/min, while various ageing durations lead to the emergence of phase transformation that occurs at different critical temperatures. Tensile loading experiments conducted using a test rig equipped with a heater revealed the evolution of mechanically induced phase transformation behaviour. Mathematical models are proposed to predict the dependence of critical temperatures and critical stresses/strains on the ageing treatment conditions and alloy composition.